ANALYSIS OF PRELIMINARY FACTORS OF TREND IMPULSIVE BUYING BEHAVIOR ON RETAIL CONSUMER IN SIDOARJOANALYSIS OF PRELIMINARY FACTORS OF TREND IMPULSIVE BUYING BEHAVIOR ON RETAIL CONSUMER IN SIDOARJO - Eva Desembrianita; Mahjudin Mahjudin; Sukaris Sukaris (Universitas 17 Agustus 1945 Surabaya, 2020)
Impulsive buying behavior occurs when consumers are in store outlets, so they feel the internal and external influences of the store's environmental situation which can affect consumers in a continuous process, especially in retail stores. The purpose of this study is to analyze internal and external influences which are the driving factors for consumers to make purchase decisions and make impulsive purchases. The population is a study of women who shop at retail stores, the sample is determined by purposive sampling method. The research method uses descriptive qualitative. The results showed the tendency of impulsive buying behavior at outlets prioritizing information by internal hedonic factors. Shopping motivation, price perception and the influence of external factors is the store environment that provides ATM facilities and the name of the consumer's money.